The Integration of Islamic Values and Betawi Cultural Wisdom in Strengthening Character Education of University Students in Jakarta through the Merdeka Curriculum and MBKM Programme in the Digital Era - Mesenu, Mesenu; Yernawilis, Yernawilis (Yayasan Insan Mulia Bima, 2025)
This study aims to thoroughly analyse how the integration of Islamic values and Betawi cultural wisdom can strengthen character education among university students in Jakarta, particularly within the implementation of the Merdeka Curriculum and the Merdeka Belajar–Kampus Merdeka (MBKM) programme in the digital and global era. The primary objective of this research is to formulate a character education framework based on local and religious values that is adaptive to the challenges of the times and relevant to the needs of 21st-century learners. This research employs a library research method with a descriptive-qualitative approach. Data were collected from various sources, including books, academic journals, online articles, and official policy documents. Mendeley was used as a reference management tool, while NVivo 12 was utilised for thematic analysis and in-depth data interpretation. The findings indicate that the integration of Islamic principles and Betawi cultural values into the curriculum structure significantly contributes to the formation of students’ character and morality. The flexibility of the Merdeka Curriculum and the MBKM programme allows for the contextual and applicable internalisation of these values. The success of this character education model largely depends on the synergy between higher education institutions, families, and communities as the three main pillars in shaping students who are morally upright, disciplined, and rooted in local culture. This study offers both theoretical and practical contributions in the form of a character education model that is contextual, rooted in local culture, and relevant to the increasingly digitalised and globalised educational landscap